ANALISIS BREAK EVEN POINT USAHATANI CENGKEH DI DESA BUYAT I KECAMATAN KOTABUNAN KABUPATEN BOLAANG MONGONDOW TIMUR - Fadhilah, Prity Dinda; Pangemanan, Paulus Adrian; Lumingkewas, Jelly Ribka Danaly (AGRI-SOSIOEKONOMI, 2022)
The purpose of this research was to analyze the Break Even Point of clove farming in Buyat I Village, Kotabunan Sub-District, East Bolaang Mongondow Regency. This research was carried out for approximately 1 month from March 2021 to April 2021. The population in this study were clove farmers in Buyat I Village, Kotabunan Sub-District, East Bolaang Mongondow Regency who cultivated cloves from 1980 with a total of 98 clove farmers and 40 landowners. The sampling process was carried out by simple random sampling method. The total sample of this study was 20, half of the population of land-owning farmers. The analysis used is the break-even point analysis. The results of this study indicate that the total production in Buyat I Village is 14,953 Kg. The total revenue from clove farming in one harvest is Rp. 1,147,230,000. The total cost incurred by clove farming in one harvest is Rp. 331,599,000. The BEP in units (TR=TC) of clove farming in Buyat I Village is 474 kg. BEP in Rupiah (TR = TC) clove farming in Buyat I Village in one harvest is Rp. 18,439.993.